Resurrecting the Go-Between: A Study of the Revived Bawd’s Challenge to Blood Purity and Christian Doctrine in Feliciano de Silva’s Segunda comedia de la Celestina - Andrea Nate (Celestinesca, 2021)
This study argues that Feliciano de Silva’s Segunda comedia de la Celestina (1534) challenges officially mandated  religious homogeneity through the figure of the go-between. Each section of the article traces the strategies of resistance of the resurrected Celestina in dialogue with Silva's connections to the converso community. A comparative, historicist approach shows how the author implicates the text in a greater discourse associated with Inquisitorial practices. I ultimately contend that the intermediary, when studied beside the woodcuts in the oldest surviving rare edition of the text, Medina del Campo 1534, operates in ways that resist notions of contamination. By examining the ways in which Silva inverts paradigms through the go-between protagonist, this study reveals how the sequel calls into question prevailing attitudes toward limpieza de sangre in sixteenth-century Spain. Finally, engaging with several theories about La Celestina's possible functions, sheds light on how sixteenth-century readers may have read the original bestselling comedy.